Two-Speed Europe Model in the Aspect of Europe 2020 Strategy - Malgorzata CWIEK; Katarzyna MAJ-WASNIOWSKA; Katarzyna STABRYLA-CHUDZIO (Communications of International Proceedings, 2020)
The purpose of the paper is to indicate if two-speed Europe is an existing and real concept in the context of the EU strategy - Europe 2020. Based on the selected indicators of: Employment, Research and Development (R&D), Climate Change and Energy, Education, Poverty and Social Exclusion, it was examined whether the division of countries corresponds to the assumptions of the two-speed Europe concept and if it is equivalent to the countries of the euro area, which is the novelty factor in the paper. Cluster analysis and Mann–Whitney U test were used in the study. It turns out that in the context of conducted research, in the EU we are dealing with a model of a Europe of two speeds, but the separation line is not equal to membership of the Eurozone, i.e. with the concept of two speeds formulated based upon political criteria.
Keywords: Two-speed Europe; Multi-speed Europe; differentiated integration; Europe 2020 Strategy; cluster analysis